Proceedings of the Thirty-Ninth Annual ACM Symposium on Theory of Computing 2007
DOI: 10.1145/1250790.1250882
|View full text |Cite
|
Sign up to set email alerts
|

Vertex cuts, random walks, and dimension reduction in series-parallel graphs

Abstract: We consider questions about vertex cuts in graphs, random walks in metric spaces, and dimension reduction in L1 and L2; these topics are intimately connected because they can each be reduced to the existence of various families of realvalued Lipschitz maps on certain metric spaces. We view these issues through the lens of shortest-path metrics on series-parallel graphs, and we discuss the implications for a variety of well-known open problems. Our main results follow.-Every n-point series-parallel metric embed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
2
1

Relationship

4
4

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 36 publications
0
14
0
Order By: Relevance
“…Despite significant progress [30,19,14,8,7], some fundamental questions are still left unanswered. As a prime example, consider the well-known planar embedding conjecture [19,20,25,27]:…”
Section: Introductionmentioning
confidence: 99%
“…Despite significant progress [30,19,14,8,7], some fundamental questions are still left unanswered. As a prime example, consider the well-known planar embedding conjecture [19,20,25,27]:…”
Section: Introductionmentioning
confidence: 99%
“…6 On its own, the established necessity of obtaining a genuinely nonlinear embedding method into low dimensions should not discourage attempts to answer Question 41, because some rigorous nonlinear dimension reduction methods have been devised in the literature; see e.g. [24,233,63,110,32,33,139,146,59,154,62,1,34,112,191,77,150,203,103,30,201,206,16]. However, all of these approaches seem far from addressing Question 41.…”
Section: Infinite Subsets Of Hilbert Spacementioning
confidence: 99%
“…It was also proved in [50] that trees, hyperbolic groups, complete simply connected Riemannian manifolds of pinched sectional curvature and Laakso graphs all have Markov type 2, and that spaces that admit a padded random partition (see [36]), in particular doubling metric spaces and planar graphs, have Markov type for all ∈ (0 2). In [10] it was shown that series parallel graphs have Markov type 2, and finally in the recent work [13] it was shown that spaces that admit a padded random partition have Markov type 2. Thus, in particular, doubling spaces and planar graphs have Markov type 2.…”
Section: Under the Assumptions Of Theorem 111 If In Addition Y Is Amentioning
confidence: 99%